The Effect of Combination of Warm Compression and Chocolate Against Menstrual Pain Reduction (Dysmenorrhea) In Teens In SMP Negeri 1 Bangkalan - Arisda candra Satriawati; Esti Nugraheny; Yuni Kusmiyati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Abstract The problem of adolescent reproduction health is still a problem that needs attention. Many women who experience discomfort in the onset of menstruation, one of them is dysmenorrhea. This study aims to find out effect of combination of warm compress and chocolate to decrease menstruation pain ( dysmenorrhea ) on raja in SMP Negeri 1 Bangkalan.This research uses Quasi Experiment method by using control time series design. The population in this study were female students of SMP Negeri 1 Bangkalan who had dysmenorrhea . Technique of sampling this research was by using simple random sampling with inclusion and exclusion criteria of 54 respondents divided into two groups with each group of 27 respondents . Data analysis was performed withch i-square test and logistic regeresi.The results showed there was influence of combination of warm and chocolate compresses to menstrual pain decrease (p-value 0,050). In addition there are other factors that affect the decrease in menstrual pain that is IMT (p-value 0.032). It is advisable to teenagers who experience menstrual pain to check the health condition of their reproductive organs if pain still occurs during menstruation.Keywords : combination of warm compresses and chocolate, menstruation pain